2017
DOI: 10.1038/nature22075
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial TLR4 and the microbiome drive cerebral cavernous malformations

Abstract: SUMMARY Cerebral cavernous malformations (CCMs) are a cause of stroke and seizure for which no medical therapies exist. CCMs arise from loss of an adaptor complex that negatively regulates MEKK3-KLF2/4 signaling in brain endothelial cells, but upstream activators of this disease pathway remain unknown. Here, we identify endothelial TLR4 and the gut microbiome as critical stimulants of CCM formation. Activation of TLR4 by gram negative bacteria or lipopolysaccharide accelerates CCM formation, while genetic or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
237
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(256 citation statements)
references
References 62 publications
7
237
3
Order By: Relevance
“…Based on 1,472 of 1,600 compounds with annotated targets in zebrafish and 4,170 of 4,748 in C. elegans , DePick predicted 47 and 134 human proteins as statistically significant targets of the compounds identified in the zebrafish and in the C. elegans screens, respectively (; ). Several of the targets identified in the C. elegans screen had previously been implicated in CCM; these included TLR4 (Tang et al , ), metalloproteinases (MMP2, MMP7, MMP13, MMP14; Zhou et al , ), and HMGCR (Nishimura et al , ), which is a strong validation of the DePick method ().…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on 1,472 of 1,600 compounds with annotated targets in zebrafish and 4,170 of 4,748 in C. elegans , DePick predicted 47 and 134 human proteins as statistically significant targets of the compounds identified in the zebrafish and in the C. elegans screens, respectively (; ). Several of the targets identified in the C. elegans screen had previously been implicated in CCM; these included TLR4 (Tang et al , ), metalloproteinases (MMP2, MMP7, MMP13, MMP14; Zhou et al , ), and HMGCR (Nishimura et al , ), which is a strong validation of the DePick method ().…”
Section: Resultsmentioning
confidence: 96%
“…The identification of these misregulated signaling pathways has suggested potential routes for pharmacological interventions, and molecules that modulate these pathways have been tested in preclinical studies of murine endothelial‐specific inducible CCM models and even in clinical studies. These studies investigated the potential of the Rho/Rock signaling inhibitors fasudil or simvastatin (Zhou et al , ; Shenkar et al , ), the blood pressure lowering drug propranolol (Reinhard et al , ), the Wnt signaling inhibitor sulindac sulfone (Bravi et al , ), the TGFβ and pSMAD inhibitors LY‐364947 and SB‐431542 (Maddaluno et al , ), the TLR4 antagonist TAK‐242 (resatorvid; Tang et al , ), or treatment with antibiotics (Tang et al , ). However, since many of these candidate drugs may cause severe side effects in patients and because a comprehensive overview of CCM‐relevant molecular pathways is still lacking, the scientific community has recognized the need of performing more systematic small‐molecule screens.…”
Section: Introductionmentioning
confidence: 99%
“…Commensal segmented filamentous bacteria (SFB), present in BL/6N, drives Th17 differentiation (Ivanov et al, 2009) and confers susceptibility to autoimmune arthritis in BL/6J by enhancing IL-17A production (Wu et al, 2010), a cytokine that disrupts TJs (Kebir et al, 2007). The gut microbiome regulates maturation of the BBB (Braniste et al, 2014) and changes the phenotypic manifestation of cerebral cavernous malformations, a CNS vascular disease, in the same genetic background (Tang et al, 2017). These factors could contribute to differences in the phenotype observed between two studies in Cav1 −/− EAE mice.…”
Section: Discussionmentioning
confidence: 99%
“…48: 564-575 In summary, this study underscored the critical role of TLR2 signaling in endothelial cells for the development of atherosclerosis. Recent work has implicated microbiota-triggered stimulation of the endothelial TLR4 signaling as a critical pathway promoting the formation of cerebral cavernous malformations, which are a cause of stroke and seizure [97]. Interestingly, antibiotic decimation of gut microbiota for 8 weeks and 3 day re-colonization before induction of a middle cerebral artery occlusion in a mouse model suggested that the microbiota status of the host might be a relevant factor defining the stroke outcome [98].…”
Section: Atherosclerosismentioning
confidence: 99%